JARE53往路流氷域での厳しい氷況の原因と今後の対策 - 田村, 岳史; 清水, 大輔; 木村, 詞明; 杉本, 風子; 杉村, 剛; 照井, 健志; 牛尾, 収輝; Tamura, Takeshi; Simizu, Daisuke; Kimura, Noriaki; Sugimoto, Fuko; Sugimura, Takeshi; et al. (2014)
conference object